Performance assessment of LUT based diffraction field calculation method for pixelated SLMs - (:unkn) unknown (OSA - The Optical Society, 2016)
Performance assessment of a look-up-table based diffraction field calculation method is presented. Look-up-tables are generated by uniform and non-uniform sampling of depth parameter. Uniform sampling policy provides better error performance. © OSA 2016.